Modular Hydroxyamide and Thioamide Pyranoside‐Based Ligand Library from the Sugar Pool: New Class of Ligands for Asymmetric Transfer Hydrogenation of Ketones. Issue 10 (20th June 2014) - Coll, Mercè; Pàmies, Oscar; Diéguez, Montserrat
Abstract A large library of pyranoside‐based hydroxyamide and thioamide ligands has been synthesized for asymmetric transfer hydrogenation in an attempt to expand the scope of the substrates to cover a broader range of challenging heteroaromatic and aryl/fluoroalkyl ketones. These ligands have the advantage that they are prepared from commercial D‐glucose, D‐glucosamine and α‐amino acids, inexpensive natural chiral feedstocks. By carefully selecting the ligand components (substituents/configurations at the amide/thioamide moiety, the position of amide/thioamide group and the configuration at C‐2), we found that pyranoside‐based thioamide ligands provided excellent enantioselectivities (in the best cases, ees of >99% were achieved) in a broad range of ketones, including the less studied heteroaromatics and challenging aryl/fluoroalkyls. Note that both enantiomers of the reduction products can be obtained with excellent enantioselectivities by simply changing the absolute configuration of the thioamide substituent. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>